Mechanism of hypolipidemic effect of rubber seed oil- Its effect on cholestrol tolerant test in rhesus monkey - Chaocai Tang; Zhixiong Zhang
Rubber seed oil is one of the plant oils rich in polyunsaturated fats. We have demonstrated that it has some hypolipidemic effects both in experimental hyperlipoidemic animals and in hyperlipoidemic patients. The present study was performed on 30 Rhesus monkeys (Macaca mulatta) which were divided in to four groups. Group 1, received lard (20 ml) and cholestrol, Group 2, rubber seed oil (20 ml) and cholestrol (2 g), Group 3, R-PuF ( 20 ml) and cholestrol ( 2 g), Group 4, normal saline ( 20 ml) alone. Following the overnight fasting, the blood samples were obtained for total cholestrol (T-ch) , triglyceride (TG) and high density lipoprotein cholestrol (HDL-ch). T-ch, TG and HDL-ch levels were determined repeatedly at 1, 2, 4 and 8 hours after the administration of a single dose of oral drugs. The results showed that following the administration of a single dose of drugs, the T-ch peak level was higher in Group 1 than in Group 2 and 3, but the blood T-ch level decreased more rapidly in Group 2 and 3 than in Group 1. In addition, lard was able to decrease HDL-ch level two hours after the administration of a single dose while rubber seed oil and R-PuF were able to increase it at the same time. These results suggested that R-PuF might be a main hypolipidemic component of rubber seed oil.
Keywords: Cholestrol tolerant test; Hypolipidemic effect; Rhesus monkeys; Rubber seed oil